2016
DOI: 10.1371/journal.pone.0168569
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Vildagliptin against Pioglitazone-Induced Bone Loss in Type 2 Diabetic Rats

Abstract: Long-term use of thiazolidinediones (TZDs) is associated with bone loss and an increased risk of fracture in patients with type 2 diabetes (T2DM). Incretin-based drugs (glucagon-like peptide-1 (GLP-1) agonists and dipeptidylpeptidase-4 (DPP-4) inhibitors) have several benefits in many systems in addition to glycemic control. In a previous study, we reported that exendin-4 might increase bone mineral density (BMD) by decreasing the expression of SOST/sclerostin in osteocytes in a T2DM animal model. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Kim and coworkers have indeed shown that sclerostin levels are increased in diabetic rats compared to controls and can be downregulated by exenatide treatment (Kim et al 2013). More recently, they demonstrate that the DPP-4 inhibitor vildagliptin lowers the increased levels of sclerostin induced by thiazolidinedione (Eom et al 2016). Our own results showed that exenatide but not liraglutide decreased sclerostin levels in OVX mice (Pereira et al 2015).…”
Section: Sclerostinsupporting
confidence: 54%
See 1 more Smart Citation
“…Kim and coworkers have indeed shown that sclerostin levels are increased in diabetic rats compared to controls and can be downregulated by exenatide treatment (Kim et al 2013). More recently, they demonstrate that the DPP-4 inhibitor vildagliptin lowers the increased levels of sclerostin induced by thiazolidinedione (Eom et al 2016). Our own results showed that exenatide but not liraglutide decreased sclerostin levels in OVX mice (Pereira et al 2015).…”
Section: Sclerostinsupporting
confidence: 54%
“…However, not all studies are showing a positive effect of DPP-4 inhibitors on fracture risk, BMD and bone turnover (Monami et al 2011, Driessen et al 2014. Recent preclinical studies showed protective effect of DPP-4 inhibitors on the skeleton of diabetic rats (Glorie et al 2014, Eom et al 2016 while others have shown no effect (Gallagher et al 2014). In vitro studies have also indicated neutral effects of DPP-4 inhibitors on bone formation (Gallagher et al 2014).…”
Section: Effect Of Dpp-4 Inhibitors On the Skeletonmentioning
confidence: 99%
“…Interestingly, pharmacologic reduction in DPP‐4 showed an improvement in the bone phenotype of mice, whereas genetically induced reduction of DPP‐4 (DPP‐4 knockout mice) was not associated with such changes . Vildagliptin was also found to have beneficial effects on BMD and bone microacrchitecture and has even been shown to restore bone changes induced by pioglitazone treatment in a T2D animal model . Another DPP‐4 inhibitor, MK‐0626, had neutral effects on bone in a T2D mouse model .…”
Section: Drugs and Bonementioning
confidence: 99%
“…289 Vildagliptin was also found to have beneficial effects on BMD and bone microacrchitecture 292 and has even been shown to restore bone changes induced by pioglitazone treatment in a T2D animal model. 293 Another DPP-4 inhibitor, MK-0626, had neutral effects on bone in a T2D mouse model. 286 Sitagliptin has not been associated with an increased risk of fracture based on published studies 265,298 and a meta-analysis that included 27 trials evaluating sitagliptin use 299 ; however, a recent cohort study with 1578 participants concluded that sitagliptin use for longer than 250 days was associated with increased risk for fracture (aHR: 1.32).…”
Section: Skeletal Effects: In Vivomentioning
confidence: 99%
“…Actually, preclinical studies have suggested a protective effect of DPP4i on bone metabolism in animals treated with pioglitazone. The administration of vildagliptin to T2DM diabetic rats restored bone mass density, trabecular bone volume and trabecular bone thickness, all parameters decreased by pioglitazone . Also, the risk of fracture can be mitigated by fall prevention and by screening and treatment of osteoporosis.…”
Section: Safety Considerations: Balance Between Risk and Benefitmentioning
confidence: 94%